DIGITALIZATION OF AUTOMOTIVE AC PRACTICUM THROUGH AN INTERACTIVE EPUB-BASED E-JOBSHEET INTEGRATED WITH QR CODE - Ratnawati, Dianna; Mindarta, Erwin Khomara; Wijaya, Robby; Subandi, Mahfudi Sahly (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
Practical learning in vocational education serves as a key driving factor in supporting the achievement of core competencies for prospective graduates of automotive education programs to meet the competency demands of the automotive industry labor market. Particularly in the era of artificial intelligence, industrial demands have shifted towards high-level digital technology literacy. Therefore, practical learning tools such as jobsheets need to be developed in digital formats. This study aims to develop an interactive e-jobsheet based on ePub integrated with QR codes, designed for effective use in automotive air conditioning (AC) practicum learning for students. The research is categorized as Research and Development (RD), employing the ADDIE model stages of Analysis, Design, Development, Implementation, and Evaluation. The results of expert validation tests showed that the average media expert assessment of the ejobsheet was 96%, indicating it is highly feasible, while the average assessment from subject matter experts was 98%, also highly feasible. Furthermore, evaluation results revealed positive student responses, with an average assessment of the e-jobsheet content at 97% (highly feasible) and an average perception rating of the e-jobsheet media at 98% (highly feasible). Thus, it can be concluded that the ePub-based e-jobsheet integrated with QR codes is highly recommended as a teaching material to support practicum learning in automotive workshops and is relevant to the needs of the automotive industry, especially in fulfilling graduate competencies in the era of Industry 4.0. This e-jobsheet also demonstrates superiority in supporting self-directed digital learning compared to conventional jobsheets.